Discovery of A New Human A(2A) Adenosine Receptor Agonist, Truncated 2-Hexynyl-4′-thioadenosine - Hou, Xiyan (American Chemical Society, 2010)
[Image: see text] The truncated C2- and C8-substituted 4′-thioadenosine derivatives 4a−d were synthesized from d-mannose, using palladium-catalyzed cross-coupling reactions as key steps. In this study, an A(3) adenosine receptor (AR) antagonist, truncated 4′-thioadenosine derivative 3, was successfully converted into a potent A(2A) AR agonist 4a (K(i) = 7.19 ± 0.6 nM) by appending a 2-hexynyl group at the C2-position of a derivative of 3 that was N(6)-substituted. However, C8-substitution greatly reduced binding affinity at the human A(2A) AR. All synthesized compounds 4a−d maintained their affinity at the human A(3) AR, but 4a was found to be a competitive A(3) AR antagonist/A(2A) AR agonist in cyclic AMP assays. This study indicates that the truncated C2-substituted 4′-thioadenosine derivatives 4a and 4b can serve as novel templates for the development of new A(2A) AR ligands.